Selection of the optimal solvent system to be used in the extraction of antioxidant compounds from hazelnut (Corylus avellana L.) kernels - Delgado, Teresa (2011)
Hazelnuts are highly nutritious and contain significant amounts of fat and protein, being reported nowadays that they are also especially rich in antioxidants. Antioxidants limit the oxidative stress that is thought to contribute to the occurrence of several human diseases. Owing to this, it is very important to search natural products with antioxidant properties to be used in the prevention of such illnesses. Numerous methods have been used to evaluate the antioxidant efficacy. Their choice depends on the chemical structure of the active components, being recommended to perform studies for selecting the best extraction technique. In this context, the main objective of this study was to optimize the extraction process, in !enns of solvent and extraction time that maximizes the extraction of total phenols and antioxidant activity of hazelnut kernels. Different experiments were conducted. In the first, phenolic compounds were extracted with boiling water (45 minutes) and methanol (room temperature for 24 and 24 + 24 hours). Higher extraction yields were obtained with water (16.7% ± 4.0) than methanol (10.2 - 14.0%). Total phenolic compounds were extracted in a higher extent in the aqueous extraction (25.6 mg gallic acid equivalents/g extract ± 9.9), than in the methanolic extractions (9.62 to 12.1 mg gallic acid equivalents/g of extract). In the second set, hazelnuts were again subjected to the extraction with water (12.4% ± 1.7) and acetone 60% (v/v) during 24, 24+24 and 24+24+24 hours. The highest extraction yields were obtained with acetone (17.8 - 29.5 %). In relation to the total phenol content, the highest value was again obtained with water (44.3 mg gallic acid equivalents/g extract ± 7.7), varying between 28.2 and 36.2 mg gallic acid equivalents/g extract in acetone extractions. In terms of antioxidant activity, acetone extracts, with EC5ll values of 1.12 10 1.53 mg/ml, showed the highest antioxidant capacity. On contrary, the methanolic extracts presented the lowest one, not being observed a significant Increase on the antioxidant activity with the increase of the extraction time. In conclusion, the results showed that hazelnut kernels have phenolic substances, as welt as antioxidant properties. However, their extraction depends on the solvent used, with acetone 80% (v/v) at room temperature during 24 hours the most promising method